CULTURAL MEANINGFULNESS ON INTERCULTURAL PERSPECTIVE OF ENGLISH LEARNING MATERIALS FOR ELEMENTARY SCHOOL - Sabilaha, Fardini; Beratha, Ni Luh Sujtiati; Budiarsa, I Made; Yadnya, Ida Bagus Putra (Aksara, 2018)
This current paper brings into discussion cultural meaningfulness on intercultural perspective of English learning materials for elementary school. Students might be perceived to master English, but there has been no guarantee that they can properly make use of their acquired language skills upon direct interaction with native speakers of the target language. This is reasonable as English instruction in elementary school is projecting grammatical aspects, not touching cultural aspects of the target language yet. In fact, those cultural aspects are playing pivotal roles in achieving interactional comprehension between speakers and interlocutors. In regards to cultural studies, foreign language students are to be apt to target languageâs cultures. Departing for the mentioned concerns, English is to be taught by incorporating cultural aspects of native speakers, and thus intercultural perspective. This current paper pinpoints the development of intercultural perspective in English learning materials for elementary school students aging from 6-12 years old. Cultural meaningfulness on intercultural perspective is set to be the target that encapsulates various topics for teaching English in elemenatry school. The so called perspective not merely comprises social skills, but training sensitivity and comprehension on values, point of view, proper way of life and thinking as well. A number of materials containing intercultural perspective and cultural meaningfulness are described in this paper. Those materials are presented within six intercultural topics in the forms of culture-related vocabularies, expressions, and meanings.